Solutions to attract investment capital for tourism development: Evidence from Vietnam economy - Huyen Le Hoang Ba; Phuong Nguyen Thi Thu; Thanh Ngo Chi; Hanh Hoang Thanh; Chinh Le Huy (Accounting, 2020)
The objective of this study is to propose solutions to attract investment capital for tourism development in Thanh Hoa province, Vietnam. Based on the theoretical framework following eclectic or “OLI model” developed by Dunning and Narula (1996) [Dunning, J., & Narula, R. (2003). Foreign direct investment and governments: catalysts for economic restructuring. Routledge.] and data of 660 questionnaires collected from a survey of tourism investors in Thanh Hoa provinces, we found some important influential factors affecting the attraction of investment for tourism development in Thanh Hoa province. In particular, the local government’s policy of attracting capital appears to have the highest level of importance. The study has some policy implications to increase the attractiveness of investment capital in tourism development in the area.